2022
DOI: 10.55230/mabjournal.v51i1.2157
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF BANANA, POTATO, AND COCONUT WATER IN THE REGENERATION OF Ficus carica cv. Japanese BTM 6

Abstract: Fig (Ficus carica L.) belongs to the family of Moraceae and its fruits are known to be nutritious to the human diet. Organic additives function as an alternative to replace conventional carbon sources besides containing other nutritional components required for plant growth. This study aims to evaluate the effects of organic additives incorporated in culture media for the regeneration of Ficus carica cv. Japanese BTM6. In vitro shoots were cultured in MS medium supplemented with 1 mg/L of BAP without sucrose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…This finding was different from that recorded in our study, where only the nutrient media containing banana puree promoted 100% rooting. The lowest percentage of rooting (50 ± 7.32-70 ± 8.61%) was observed in treatments fortified with potato puree, which occurred probably because potato puree contains large quantities of starch that interferes and prevents the absorption of nutrients, as it acts as a gelling agent in the nutrient medium (Lee et al, 2022). The results showed that the interaction between organic additives and auxin type affected plant height, number of leaves, number of adventitious shoots, number of roots, and their length.…”
Section: Rooting Of Plantletsmentioning
confidence: 95%
“…This finding was different from that recorded in our study, where only the nutrient media containing banana puree promoted 100% rooting. The lowest percentage of rooting (50 ± 7.32-70 ± 8.61%) was observed in treatments fortified with potato puree, which occurred probably because potato puree contains large quantities of starch that interferes and prevents the absorption of nutrients, as it acts as a gelling agent in the nutrient medium (Lee et al, 2022). The results showed that the interaction between organic additives and auxin type affected plant height, number of leaves, number of adventitious shoots, number of roots, and their length.…”
Section: Rooting Of Plantletsmentioning
confidence: 95%
“…Komposisi media MS dinilai lengkap karena mengandung berbagai unsur hara yang dibutuhkan oleh tumbuhan seperti garam mineral tinggi dan senyawa N dalam bentuk amonium dan nitrat (Anitasari et al, 2018). Komposisi media MS dengan penambahan suplemen zat pengatur tumbuh (ZPT) seperti NAA (naphthaleneacetic acid) dan BAP (6benzylaminopurine) karena kemampuannya dalam menstimulus pertumbuhan (Lee et al, 2022). Misalnya untuk meregulasi pembelahan sel, memacu organogenesis, perkembangan kloroplas, menginduksi embriogenesis dan organogenesis (Markal et al, 2015).…”
Section: Pendahuluanunclassified
“…Hal ini mengindikasikan bahwa air kelapa dapat menstimulasi dan memaksimalkan BAP dalam menginduksi pertumbuhan sel pertumbuhan meristem pada anggrek Tebu. BAP akan bekerja lebih efektif dalam pembelajan sel bila dikombinasikan dengan hormon sitokinin yang terkandung dalam air kelapa (Lee et al, 2022). Hal ini berkaitan dengan kandungan hormon sitokinin dalam air kelapa yang dapat menstimulasi pembelahan sel secara berkelanjutan sehingga terbentuk tunas baru pada anggrek tebu.…”
Section: Hasil Dan Pembahasan Waktu Muncul Tunas Anggrek Tebuunclassified
“…Both fresh and dried fig fruits are edible. In addition to being used as a food source, certain Ficus species are utilized as medicines in Ayurvedic and traditional Chinese medicine (Lee et al, 2022). Fig is said to have nutritional value to humans as it is cholesterol-free and an excellent source of minerals, vitamins, and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%